(untitled) (Contemporary Mathematics, 2025)
In this paper, we consider an extension of the record model, which is well known as the K-record. For the Random Variables X and Y, the stress-strength parameter R = P(Y < X), and the EFWE distribution is applied, when the random variables X and Y approach the Exponential Flexible Weibull Extension (EFWE) distribution, which is an extension of the exponential flexible Weibull distribution. The behavior of stress-strength parameters and reliability have been estimated using the k-record data by using maximum likelihood and Bayesian estimators through the Monte Carlo simulation study, which showed satisfactory performance of the estimators. Finally, the stress-strength model of the EFWE distribution is utilized to analyze the actual data that shows the failure times of two distinct types of electrical insulators.